Programmed Cell Death Ligand 1 (PD-L1) and major Histocompatibility Complex Class I (MHC Class I) Expression Patterns and Their Pathologic Associations in triple-Negative Breast Cancer - Kaewkedsri P; Intarawichian P; Jessadapattarakul S; Kunprom W; Koonmee S; Thanee M; Somintara O; Wongbuddha A; Chadbunchachai P; Nawapun S; Aphivatanasiri C (Breast Cancer: Targets and Therapy)
Ponkrit Kaewkedsri,1 Piyapharom Intarawichian,1 Sirawich Jessadapattarakul,1 Waritta Kunprom,1 Supinda Koonmee,1 Malinee Thanee,1 Ongart Somintara,2 Anongporn Wongbuddha,2 Payia Chadbunchachai,3 Supajit Nawapun,3 Chaiwat Aphivatanasiri1 1Department of Pathology, Faculty of Medicine, Khon Kaen University, Khon Kaen, Thailand; 2Department of Surgery, Faculty of Medicine, Khon Kaen University, Khon Kaen, Thailand; 3Department of Radiology, Faculty of Medicine, Khon Kaen University, Khon Kaen, ThailandCorrespondence: Chaiwat Aphivatanasiri, Department of Pathology, Faculty of Medicine, Khon Kaen University, Khon Kaen, Thailand, Email chaiap@kku.ac.thPurpose: This study aims to investigate the clinicopathological characteristics of triple-negative breast cancer (TNBC) in relation to programmed cell death ligand 1 (PD-L1) and major histocompatibility complex class I (MHC class I) expression, with a focus on their prognostic significance.Patients and Methods: A retrospective analysis was conducted on formalin-fixed paraffin-embedded (FFPE) tissue samples from 148 TNBC patients diagnosed between 2008 and 2021. Immunohistochemical analysis evaluated PD-L1 and MHC class I expression. PD-L1 was assessed using Combine Positive Scores (CPS), with the threshold set at CPS ≥ 1 and CPS ≥ 10. MHC class I expression was categorized into low and high levels. Associations between these markers, clinicopathological features, overall survival (OS), and disease-free survival (DFS) were analyzed. PD-L1 expression was also compared between older FFPE blocks (2008– 2018) versus newer blocks (2019– 2021).Results: PD-L1 expression was observed in 29.1% of cases with a Combined Positive Score (CPS) ≥ 1 and 8.8% of CPS ≥ 10 cases. MHC class I expression was evenly split between low and high levels. Older FFPE blocks (2008– 2018) showed lower PD-L1 expression than newer blocks (2019– 2021). There was no significant association between PD-L1 expression and overall survival (OS) or disease-free survival (DFS). However, high MHC class I expression was strongly associated with improved OS (HR = 0.469, 95% CI: 0.282– 0.780, p=0.004). Patients with negative PD-L1 and high MHC class I expression had the most favorable prognosis, with significant OS for CPS ≥ 1 (HR = 0.447, 95% CI: 0.236– 0.846, p=0.013) and CPS ≥ 10 (HR = 0.516, 95% CI: 0.307– 0.869, p=0.013).Conclusion: These findings support the potential of PD-L1 and MHC class I expression as prognostic markers for TNBC, offering insights to guide treatment decisions and improve patient outcomes.Keywords: triple-negative breast cancer, TNBC, programmed cell death ligand 1, PD-L1, major histocompatibility complex class I, MHC class I, immunohistochemistry, prognosis